Effects of network capabilities on firm performance across cultures - Julie Papastamatelou; Rainer Busch; Begüm Ötken; Elif Yolbulan Okan; Karim Gassemi (International Journal of Management and Economics, 2016)
The purpose of this study is to identify key factors related to network capabilities that enhance the performance of Chinese, Turkish and German firms. Chinese (n = 107), Turkish (n = 129) and German (n = 109) MBA-students completed a questionnaire, based on an earlier version developed by Kenny [2009], which included questions on the respective firm, its performance and network capabilities. The predictors of firm performance varied by country: in China "information sharing" and "trust" were important, in Turkey "network coordination" and in Germany "human capital resources." In addition, each country had its own specific drivers of firm performance. The findings of this paper should enhance understanding of the cross-cultural differences and assist managers when planning to join foreign corporations.
Keywords: M2; F2; 650; culture; firm performance; Hofstede dimensions; networks; network capabilities; organizational culture